2010
DOI: 10.1002/cncy.20082
|View full text |Cite
|
Sign up to set email alerts
|

Paired box gene 8, HBME‐1, and cytokeratin 19 expression in preoperative fine‐needle aspiration of papillary thyroid carcinoma

Abstract: BACKGROUND:Paired box gene 8 (PAX8), a member of the thyroid‐specific transcription factors, has recently been investigated as a useful marker of thyroid epithelial neoplasms. To the authors' knowledge, its utility in the immunohistochemistry of papillary thyroid carcinoma (PTC) has not been well studied to date. The goal of the current study was to compare the immunohistochemical expression of PAX8 with HBME‐1 and cytokeratin 19 (CK19) expression on cell block preparations of PTC and benign thyroid nodules (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 17 publications
(35 reference statements)
0
34
0
Order By: Relevance
“…Two cases Table 1 PAX8 positivity in cell blocks and histological sections. Staining intensity and distribution were scored based on the method of Schmitt et al (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two cases Table 1 PAX8 positivity in cell blocks and histological sections. Staining intensity and distribution were scored based on the method of Schmitt et al (14).…”
Section: Discussionmentioning
confidence: 99%
“…Negative controls were obtained by omitting the primary antibody. The intensity and distribution of PAX8 staining were scored according to the method of Schmitt et al (14). Briefly, !5% of positive nuclei was considered negative, 5-10% focal positive, 10-50% intermediate and R50% diffuse.…”
Section: Pax8 Immunocytochemistrymentioning
confidence: 99%
“…Most studies demonstrated that overexpression of CK19 is mainly related to papillary thyroid cancer with a positive rate, accounting for 70-100% of all cancers (Flanagan et al 2008, Krzeslak et al 2008, Barut et al 2010, Gong et al 2012. Furthermore, CK19 has been used in combination with PAX8 and HBME1 to increase the specificity of diagnosis for thyroid tumors by FNA (Schmitt et al 2010, Cochand-Priollet et al 2011. The upregulated expression of CK8 and CK19 was detected in Nthy-ori 3-1 cells transfected with PPFP, which may indicate that involvement of CK8 and CK19 is induced by PPFP in the malignant transformation and enhanced migration of thyroid cells.…”
Section: Endocrine-related Cancermentioning
confidence: 99%
“…Sangoi et al [6] proposed replacing CD10 and RCC markers with PAX2 and PAX8 as markers in the workup for potential metastatic renal tumors, and Ozcan et al [7] supported this by suggesting that PAX2 and PAX8 are the best markers for metastatic RCCs. An additional use for PAX8 is that, since PAX8 is expressed in thyroid follicular cells, it will be positive in cytologic specimens of metastatic thyroid malignancies [1,12,22,28]. This is exemplified by the case of Hürthle cell carcinoma in the pleural fluid, which had strong nuclear positivity for PAX8 but not for PAX2.…”
Section: Discussionmentioning
confidence: 99%